The influence of acute hypoxia on the prediction of maximal oxygen uptake using multi-stage shuttle run test - Neya, M.; Ogawa, Y.; Matsugaki, N.; Kimura, K.; Yoshida, R.; Kobayashi, K. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The purpose of this study was to investigate changes in predicted maximal oxygen uptake (VO2max) by the multistage shuttle run test (MSSR) and several physiological parameters in MSSR under normoxia and two hypoxic conditions and the influences of acute hypoxia on these changes in MSSR. METHODS: Experimental design: six college long distance runners (LR), seven college rugby athletes (RG) and eight untrained college males (UM) performed incremental running test on the treadmill and MSSR in 17.5% (HYP17.5%) and 15.5% (HYP15.5%) of oxygen concentration and normoxia (NOR20.9%). Measures: VO2max was measured by the treadmill protocol and predicted by MSSR. Maximal heart rate (HRmax) and maximal blood lactate concentration (BLamax) were recorded at the termination of each test. RESULTS: Significant correlation was observed between measured VO2max by the treadmill protocol (57.2+/-8.3 ml x kg-1 x min-1) and predicted VO2max in NOR20.9% (54.6+/-8.0 ml x kg-1 x min-1) (r=0.80, p<0.05). Also strong correlations in predicted VO2max between NOR20.9% and HYP17.5% (51.1+/-8.0 ml x kg-1 x min-1) (r=0.90, p<0.05) and between NOR20.9% and HYP15.5% (48.1+/-7.3 ml x kg-1 x min-1) (r=0.82, p<0.05) were observed. CONCLUSIONS: The results show that although MSSR underpredicts VO2max, it is effective to evaluate aerobic power and can detect the influence of oxygen concentration on aerobic power. The specific movement of MSSR may affect the performance of LR but MSSR can describe the influence of hypoxia on the performance of LR compared to normoxia. Thus MSSR can be used to evaluate the influence of hypoxia or altitude on aerobic power as a field test.